Pengaruh Current Ratio, Debt To Equity Ratio, Return On Assets Terhadap Nilai Perusahaan ( Studi Empiris pada Perusahaan Sub Batubara yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Ristikasari, Danin; Wulandari, Ika (Jurnal Ilmiah Wahana Pendidikan, 2023)
This Research aims to analyze the influences of the current ratio, debt to equity ratio and return on assets registered on the Indonesia Stock Exchange 2019-2021. The ability of a company to analyze can be utilized as a pattern of a company in making a decision. The total sample used in this research is 19 Companies that used report data for three years. The type of this research is quantitative method research with the explanatory approach. The data analysis method is multiple linear regression analysis. The result of this research show that Current Ratio (CR) does not influence the companies values, Debt to Equity Ratio (DER), Return On Asset (ROA) simultaneously influence the companies value on coal sub sector companies in 2019-2021.